2016
DOI: 10.3390/diagnostics6020016
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Age and Illness Duration in Chronic Fatigue Syndrome

Abstract: Chronic fatigue syndrome (CFS) is a debilitating illness, but it is unclear if patient age and illness duration might affect symptoms and functioning of patients. In the current study, participants were categorized into four groups based upon age (under or over age 55) and illness duration (more or less than 10 years). The groups were compared on functioning and symptoms. Findings indicated that those who were older with a longer illness duration had significantly higher levels of mental health functioning tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…Nacul et al suggested that the physical role item might be an adequate measure of outcome in CFS/ME, since it was the most affected [33]. Patients in our series had a poorer QoL (as measured by the SF-36 questionnaire) than CFS/ME patients from similar backgrounds reported in three previous studies [33, 3537]. As a difference, scores on the items in Nacul et al’s study [33] showed less variability than those of the other comparative studies, including ours.…”
Section: Discussionmentioning
confidence: 51%
“…Nacul et al suggested that the physical role item might be an adequate measure of outcome in CFS/ME, since it was the most affected [33]. Patients in our series had a poorer QoL (as measured by the SF-36 questionnaire) than CFS/ME patients from similar backgrounds reported in three previous studies [33, 3537]. As a difference, scores on the items in Nacul et al’s study [33] showed less variability than those of the other comparative studies, including ours.…”
Section: Discussionmentioning
confidence: 51%
“…In a cross-sectional survey of ~500 subjects, Chu et al (141) found low, non-significant Pearson correlation coefficients of 0.025 and 0.019 when SF-36 PF scores were plotted against age and duration of illness. In fact, Komaroff (142) found slight improvements in SF-36 PF when following one cohort of 99 subjects over a decade and both Tiersky (20) and Kidd (125) mentioned that long-suffering subjects might develop better psychological coping techniques. One study (143) did indicate increased fatigue, autonomic symptoms and depression in older subjects relative to younger ones but it is unclear how this study's conclusion might apply to the question at hand since they emanate from a sample who did not develop ME/CFS until they were 55 years of age or older, 15–20 years beyond the mean age of ME/CFS onset.…”
Section: Function Is Low But Appears Stable Over Timementioning
confidence: 99%
“…Giving to the fact that ME/CFS is a heterogeneous illness, many studies tried to subtype ME/SFC patients according to various clinical variables such as number of symptoms 6 , type of fatigue 7 , mode of illness onset 8 , age at onset 9 , and illness course. Biological variables were also used to group ME/CFS patients including natural killer cell activity 10 , cytokines 11 , and gene expression in the peripheral blood 12 .…”
Section: Introductionmentioning
confidence: 99%